Effects of Heat Treatments of Rosella Seeds (Hibiscus Sabdariffa, Linn) and the Presentation of Diets Containing them on Zootechnical and Economic Performances of Broilers in Dakar Region (Senegal): - Ayssiwede, Simplice Bosco; Abodi, Koffi Elemawussi; Atchiwassa, Sodjinin; Bonou, Mahou-hognon Cyrille; Missohou, Ayao (Indian Journal of Animal Nutrition, 2023)
This study carried out in Sangalkam from March to April 2019, aims to assess the effects of heat treatments of rosella seeds and the presentation of diets containing them on growth performance and economic margins of broilers. It involved 400 unsexed Coob500 strain chicks of two-weeks-old, randomly distributed into 8 groups of 50 birds each, corresponding to 8 iso-protein and iso-energetic experimental diets consisting of 4 floury (HSF0, HSCF15, HSTF15, HSBF15) and 4 granulated (HSG0, HSCG15, HSTG15, HSBG15) containing respectively 0% (control), 15% of raw, roasted and boiled rosella seeds in partial substitution of groundnut cake. At 6 weeks of age, data obtained per dietary treatment, were subjected to one-way ANOVA, completed by Duncan's Multiple Range Test at 5% error risk level. The results showed that the live body weight, daily feed intake and carcass weight of broilers fed granulated diets (HSG) were higher (p